2016
DOI: 10.18632/oncotarget.8888
|View full text |Cite
|
Sign up to set email alerts
|

AURKA induces EMT by regulating histone modification through Wnt/β-catenin and PI3K/Akt signaling pathway in gastric cancer

Abstract: Gastric cancer, a highly invasive and aggressive malignancy, is the third leading cause of death from cancer worldwide. Genetic association studies have successfully revealed several important genes consistently associated with gastric cancer to date. However, these robust gastric cancer-associated genes do not fully elucidate the mechanisms underlying the development and progression of the disease. In the present study, we performed an alternative approach, a gene expression-based genome-wide association stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…The results indicated that AURKA was a hub gene based on linkage analysis (25). Considering previous studies, we hypothesized that there may exist some genes that are co-activated with AURKA in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that AURKA was a hub gene based on linkage analysis (25). Considering previous studies, we hypothesized that there may exist some genes that are co-activated with AURKA in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, we analyzed the 184 differentially expressed genes in gastric cancer from the eGWAS and revealed AURKA is at the core of the gastric cancer linkage network (25). AURKA is a serine/threonine kinase that localizes to spindle poles, and ensures the correct assembly of cellular components during mitosis in normal cells (26).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that apart from the Smad pathway, TGF- β -related protein also activates other signaling pathways, such as MEK/ERK, Wnt/ β -catenin, and PI3K/Akt [35, 36]. Further investigations into the relationships between ginsenoside Rg1 and Smad-independent pathways are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin is the key transcriptional activator in the canonical Wnt signalling pathway in the nucleus, and HuR represses Wnt/β-catenin-mediated transcriptional activity by promoting the cytoplasmic localization of β-catenin48. Therefore, EMT appears to be regulated by the Wnt/β-catenin pathway4950. These results, combined with the change in WNT3 and WNT5B expression with alterations in SPRY4-IT1 expression in HTR-8/SVneo cells, indicate that SPRY4-IT1 might regulate the EMT in trophoblast cells through Wnt/β-catenin signalling.…”
Section: Discussionmentioning
confidence: 99%